Examining bedtime procrastination, study engagement, and studyholism in undergraduate students, and their association with insomnia - Alshammari, Tahani K.; Rogowska, Aleksandra M.; Basharahil, Raghad F.; Alomar, Sumayyah F.; Alseraye, Sarah S.; Al Juffali, Lobna A.; Alrasheed, Nouf M.; Alshammari, Musaad A. (Frontiers in Psychology, 2023)
Introduction Compulsive overstudying, known as studyholism, is an emerging behavioral addiction. In this study, we examine the prevalence of, and the relationships between, insomnia, study engagement, studyholism, bedtime procrastination among undergraduate students. Methods The Studyholism (SI-10), Athens Insomnia (AIS), and bedtime procrastination scales were administered to a convenience sample of 495 university students. Results Our findings indicate that the prevalence of insomnia was 75.31%, high studyholism was found in 15.31% of the sample, and increased study engagement was detected in 16.94%. Gender differences analysis revealed that females reported higher studyholism and bedtime procrastination than males. Fifth-year students had higher levels of studyholism than internship (p < 0.001), first-year (p < 0.01), and sixth-year students (p < 0.05). Insomnia was positively related to studyholism and bedtime procrastination. Furthermore, insomnia can be positively predicted by studyholism and bedtime procrastination. Participants with a medium level of studyholism were twice as likely to experience insomnia as those with a low level. Studyholics were six times more susceptible to insomnia than students with low studyholism levels. Compared to individuals with low bedtime procrastination levels, those with medium and high bedtime procrastination were twice as likely to report insomnia. Conclusion Our study highlights the interplay between insomnia, studyholism, and bedtime procrastination. Further, the findings indicate the need to increase awareness of insomnia.